Improving Elementary School Students' Achievement through Development of Savi- based Thematic Instructional Media - Husain, Rusmin; M, Herni (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this qualitative study was to examine the effectiveness of the development of thematic lesson plan with SAVI (somatic, auditory, visual, intellectual) model to improve learning outcomes of fifth-grade students of SD 7 State Elementary School in Lemito. The model of this study was a research and development, which adapted 4-D (define, design, develop, disseminate) model by Triagarajan, Semmel, and Semmel. Further, the testing of the developed media was carried out in three steps, namely individual testing, small-scale testing, and field testing. All data were collected from the validation sheets of the instructional media, observation sheets of students’ activities, and evaluation tests. The result of the simulation and limited testing indicated that the implementation of the thematic lesson plan with the SAVI model was effective in enhancing students’ achievement in learning; it was in a high category. For this reason, it was expected that the developed lesson plan would be used in schools for a better learning performance of the students.